Melting of 2D liquid crystal colloidal structure - Brodin, A.; Nych, A.; Ognysta, U.; Lev, B.; Nazarenko, V.; Škarabot, M.; Muševič, I. (Condensed Matter Physics, 2010)
Using video microscopy, we investigated melting of a two-dimensional colloidal system, formed by glycerol droplets at the free surface of a nematic liquid crystalline layer. Analyzing different structure correlation functions, we conclude that melting occurs through an intermediate hexatic phase, as predicted by the Kosterlitz-Thouless-Halperin-Nelson-Young(KTHNY) theory. However, the temperature range of the intermediate phase is rather narrow, <1°C, and the characteristic critical power law decays of the correlation functions are not fully developed. We conclude that the melting of our 2D systems qualitatively occurs according to KTHNY, although quantitative details of the transition scenario may partly depend on the details of interparticle interaction.